Job security and the age-composition of employment: Evidence from Chile - Carmen Pagés; Claudio E. Montenegro (Estudios de Economía, 2007)
This paper develops and tests a mechanism by which job security affects the age-composition of employment. This mechanism is based on the relative costs of dismissing young versus older workers resulting from job security provisions that are related to tenure. Using 39 consecutive annual household-surveys from Chile, we find that job security is associated with a substantial decline in the wage employment-to-population rate of young workers. In contrast, we do not find such a decline in young self-employment rates or in the wage employment rates of older workers. Comparing results for men and women and using measures of relative dismissal costs, we find that the adverse effect of job security on youth employment is driven by the link between severance payments and tenure. We also find that job security does not have a significant impact on overall aggregate employment, participation or unemployment rates.
Keywords: E24; J23; J65; 330; job security; employment composition; severance pay; Chile; job tenure